The electrochemical reduction of 1,4-benzoquinone in 1-ethyl-3-methylimidazolium bis(trifluoromethane-sulfonyl)-imide, [C(2)mim][NTf2]: A voltammetric study of the comproportionation between benzoquinone and the benzoquinone dianion - Wang, Y; Rogers, E; Belding, SR; Compton, R (2010)
The two-step electrochemical reduction of 1,4-benzoquinone, BQ, was investigated on a microdisk electrode (10 μm diameter Au) in the room temperature ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethane- sulfonyl)-imide, [C2mim][NTf2], over a wide range of scan-rates. Two reduction peaks were observed, corresponding to the reduction of BQ to the radical anion, BQ-, at a peak potential, Ep of approximately -0.50 V, followed by reduction to the dianion, BQ2- at more negative potentials (Ep ≈ -0.89 V):BQ+e-BQ-BQ-+e-BQ2-The technique of potential step chronoamperometry was used to measure the diffusion coefficients of each of the three reaction species, BQ, BQ- and BQ2-, and values of 4.73 (±0.10) × 10-11, 1.73 (±0.08) × 10-11 and 1.55 (±0.15) × 10-11 m2 s-1 were determined, respectively, at 298 K. This technique, together with cyclic voltammetric simulations, allows elucidation of the kinetic and thermodynamic parameters for both reduction processes and the following homogeneous comproportionation process:BQ2-+BQ2BQ- including the Gibbs energy, ΔG°comp, for the reaction, where a value of -38.3 kJ mol-1 suggests that the comproportionation of BQ 2- and BQ, to form BQ- is thermodynamically downhill. © 2010 Elsevier B.V. All rights reserved.